2023
DOI: 10.3390/cancers15092643
|View full text |Cite
|
Sign up to set email alerts
|

Rising Trend in the Prevalence of HPV-Driven Oropharyngeal Squamous Cell Carcinoma during 2000–2022 in Northeastern Italy: Implication for Using p16INK4a as a Surrogate Marker for HPV-Driven Carcinogenesis

Abstract: Background: The prevalence and incidence of oropharyngeal squamous cell carcinomas (OPSCCs) driven by human papillomavirus (HPV) infection are increasing worldwide, being higher in high-income countries. However, data from Italy are scanty. p16INK4a overexpression is the standard in determining HPV-driven carcinogenesis, but disease prevalence impacts on its positive predictive value. Methods: This is a multicenter retrospective study enrolling 390 consecutive patients aged ≥18 years, diagnosed with pathologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 47 publications
1
0
0
Order By: Relevance
“…CDKN2A, also known as cyclin dependent kinase inhibitor 2A/p16, plays an important role in the occurrence and development of head and neck squamous cell carcinoma (HNSCC) and is a well-known tumor suppressor gene, particularly in HPV-related HNSCC. [15,16] Our study also found that low CDKN2A expression in TSCC was significantly associated with a poor prognosis (Figure S1B, Supplemental Digital Content, http://links.lww.com/MD/K753 and Figure S2B, Supplemental Digital Content, http://links.lww.com/MD/K754), indicating the importance of CDKN2A in TSCC. CAs are a class of large zinc metalloenzymes that catalyze the reversible hydration of carbon dioxide and participate in a variety of biological processes.…”
Section: Discussionsupporting
confidence: 65%
“…CDKN2A, also known as cyclin dependent kinase inhibitor 2A/p16, plays an important role in the occurrence and development of head and neck squamous cell carcinoma (HNSCC) and is a well-known tumor suppressor gene, particularly in HPV-related HNSCC. [15,16] Our study also found that low CDKN2A expression in TSCC was significantly associated with a poor prognosis (Figure S1B, Supplemental Digital Content, http://links.lww.com/MD/K753 and Figure S2B, Supplemental Digital Content, http://links.lww.com/MD/K754), indicating the importance of CDKN2A in TSCC. CAs are a class of large zinc metalloenzymes that catalyze the reversible hydration of carbon dioxide and participate in a variety of biological processes.…”
Section: Discussionsupporting
confidence: 65%